Exclusion within Inclusive Education Policy: The Challenges Facing Urban Refugees in Accessing Education in Thailand - KARIM, MST UMME HABIBA FAHMINA, Dr. (UI Scholars Hub, 2024)
Despite Thailand’s adoption of the Education for All policy in 2005, which grants all children, including refugees, access to free public education, refugee children largely remain excluded. Camp-based refugees attend informal, unrecognized education programs, while urban refugee children are categorised with migrant children in enrollment data. In 2023, only 34% of legal migrant children were enrolled in public schools, while refugees—often classified as